2023
DOI: 10.1111/1365-2745.14064
|View full text |Cite
|
Sign up to set email alerts
|

Plastic responses of below‐ground foraging traits to soil phosphorus‐rich patches across 17 coexisting AM tree species in a subtropical forest

Abstract: Below‐ground plastic responses to soil nutrient ‘hot‐spots’ form a key nutrient foraging strategy of plants coexisting in natural ecosystems. However, it is unclear how plant species differ in these below‐ground plastic responses and how they covary. Plastic responses to soil phosphorus (P)‐rich patches of absorptive root, mycorrhizal, and exudation traits of 17 coexisting arbuscular mycorrhizal (AM) tree species in a subtropical evergreen broad‐leaved forest were investigated using a root bag method. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…Besides, warming-induced soil drying can limit the mobility of soil P (He & Dijkstra, 2014) due to P adsorption to iron oxides, hydroxides and clays in drier soils (Tian et al, 2023), and the longer and more tor- which reduces soil P availability. Warming-reduced fine root exudation, as reported in our previous study (Xiong et al, 2020), might also have contributed to decreased soil P availability and weakened uptake of P by fine roots, because the secretion of phosphatases and organic acids in root exudates solubilizes and mineralizes inorganic and organic P in the rhizosphere (Bengtson et al, 2012;Zhu et al, 2023).…”
Section: Responses Of Fine Root N and P Concentrations To Soil Warmingmentioning
confidence: 59%
“…Besides, warming-induced soil drying can limit the mobility of soil P (He & Dijkstra, 2014) due to P adsorption to iron oxides, hydroxides and clays in drier soils (Tian et al, 2023), and the longer and more tor- which reduces soil P availability. Warming-reduced fine root exudation, as reported in our previous study (Xiong et al, 2020), might also have contributed to decreased soil P availability and weakened uptake of P by fine roots, because the secretion of phosphatases and organic acids in root exudates solubilizes and mineralizes inorganic and organic P in the rhizosphere (Bengtson et al, 2012;Zhu et al, 2023).…”
Section: Responses Of Fine Root N and P Concentrations To Soil Warmingmentioning
confidence: 59%
“…To compensate for the decline in nutrient‐scavenging capability of absorptive fine roots, the three studied Pinus species showed convergence in increasing root‐exudation rates (Figure 4b), in line with previous research reporting that the importance of nutrient‐mining strategies driven by root exudation increases during tropical forest succession (Rondina et al., 2019) and pedogenesis (Zemunik et al., 2015). Moreover, a recent study showed that tree species with thicker absorptive fine roots release more root exudates than those with thinner absorptive fine roots in response to nutrient‐rich patches among 17 coexisting subtropical tree species (Zhu, Yao, et al., 2023). Collectively, these results suggest that changes in root morphological traits may be a key factor underlying shifts from an extensive to an intensive root nutrient‐acquisition mode with stand development across the three Pinus species.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the high C cost for root con- et al, 2019) and pedogenesis (Zemunik et al, 2015). Moreover, a recent study showed that tree species with thicker absorptive fine roots release more root exudates than those with thinner absorptive fine roots in response to nutrient-rich patches among 17 coexisting subtropical tree species (Zhu, Yao, et al, 2023). Collectively, these results suggest that changes in root morphological traits may be a key factor underlying shifts from an extensive to an intensive root nutrient-acquisition mode with stand development across the three Pinus species.…”
Section: Shifting Towards An Intensive Nutrient-acquisition Mode Duri...mentioning
confidence: 99%
See 2 more Smart Citations